Medical Conditions of Wild Virginia Opossums (Didelphis virginiana) - Santamaria–Bouvier, Ariane (Wildlife Rehabilitation Bulletin, 2012)
While the Virginia opossum is a frequent admission for wildlife caretakers, there is limited published information on diseases of this animal. A review of noninfectious and infectious diseases of the Virginia opossum and reported treatment options highlights what is known and the need for further data on this North American marsupial species.